Data supporting: 'Prediction of Combined Sorbent and Catalyst Materials for SE-SMR, Using QSPR and Multitask Learning' - Nkulikiyinka, Paula (Cranfield University, 2022)
Databases and key
Keywords: 'Carbon Capture Processes'; 'catalysts'; 'adsorption'; 'machine Learning Predictions'